Synthesis and characterization of activated carbon and manganese-based oxide/layered double hydroxide materials for supercapacitor applications - Manyala, Ncholu I. (University of Pretoria, 2018)
The aim of this study is to synthesize and characterize cheap, efficient and high-performance 3D activated carbon (AC) from cork (Quercus Suber) by KOH and KHCO3 activation respectively, Co-Mn LDH and MnO2-CNT nanocomposite materials with meso/microporous structures for energy storage application. The AC derived from cork (Q.suber) was synthesized with KOH in order to investigate the electrochemical performance of the AC in relation to KOH activation concentration and the AC synthesized by KHCO3 device because both materials performed well in 1 M KOH alkaline electrolyte, while ACKOH was chosen as the negative electrode in the MnO2-CNT//ACKOH device because both materials showed good performance in 1 M Li2SO4 neutral electrolyte. The aim of the hybrid devices was to take advantage of the individual working potentials of the electrode materials for enhanced electrochemical performance. All devices tested displayed energy densities ranging from 14 - 25 Wh kg-1 with corresponding power densities ranging from 450 – 500 W kg-1 at a specific current of 0.5 Ag-1 in the operating voltage window of between 1.6 V and 2.0 V in aqueous electrolyte media. All the materials tested displayed 99.7% - 100 % long-term cycling stability, showcasing the potential use of these materials as electrode materials for electrochemical capacitors.